The Impact of Career Path Development on the Organizational Commitment: “A Field Study on Ministries and Agencies in the State of Qatar” - Al-Hajri, Mohammed Khaled (Journal of Organizational Psychology, 2020)
This study aims mainly to analyze the impact of career path development on organizational commitment by providing a theoretical and practical framework on the concept of career path development for the sector under study in terms of its nature, philosophy and areas, the importance of its adoption, implementation strategies and related standards, and its impact on organizational commitment through the development of a list Questionnaire and use of Spearman's correlation coefficients, and the simple and gradual regression model to study the impact of independent variables, namely (career path development - integrated job description cards - training programs - use of skills stocks) on the dependent variable organizational commitment (emotional commitment - ongoing commitment - normative commitment) and is a community The study in workers in ministries and government agencies in the State of Qatar in accordance with demographic changes, and the study concluded, "There is a fundamental effect of the dimensions of career path development on the dimensions of the organizational commitment in the sector under study." The State of Qatar under study.